Hegemons, empires, and their elites - Lachmann, Richard (2014)
I compare ancient with modern empires and show why hegemony beyond the militaryrealm is possible only in the modern capitalist world. I examine Germany, Spain and France, whichfailed to achieve hegemony, along with the three successive hegemons: the Netherlands, Britain,and the United States. I identify the elites that were created and strengthened by their homepolity’s empire or hegemony, and enumerate the factors that allowed some colonial elites to achievehigh levels of autonomy. Colonial elite autonomy or high levels of elite unity in the metropoleprevented or undermined hegemony.